Growth and Instability Analysis of Vegetables in West Bengal, India - Dhakre, D. S.; Bhattacharya, D. (International Journal of Bio-resource and Stress Management, 2013)
The present study is related to the growth and instability of area, production and productivity of vegetables in west Bengal. The study is based on secondary data of vegetables pertaining to various vegetables as a whole for the period of 1997-98 to 2010-11. It has been observed that the growth of area, production and productivity for all vegetables registered are positive and statistically significant and instability index for all the vegetables are also positive, which indicate that there is less risk for cultivation in the state. Compound growth rate in case of productivity for cabbage and cauliflower has been noticed negative but significant. The increase in production is due to increase in area as well as interaction of area and productivity of vegetables in the state.